Daily gridded soil moisture simulations on a 1 km resolution grid covering Baden-Württemberg - Tijdeman, Erik; Menzel, Lucas (Universität, 2021)
The dataset contains gridded daily soil moisture simulations for Baden-Württemberg. The simulations were caried out with the hydroloigcal model TR...